Hello.

Asked by akshay2703 | 9th Jul, 2009, 07:49: PM

Expert Answer:

f(x+t) = 1/2 + [f(x) - f2(x)]

f(x+2t) = f((x+t)+t) 

= 1/2 + [f(x+t) - f2(x+t)]

= 1/2 + {[1/2 + [f(x) - f2(x)]] - [1/2 + [f(x) - f2(x)]]2}

= 1/2 + {[1/2 + [f(x) - f2(x)]] - [1/4 + [f(x) - f2(x)] + f(x) - f2(x)]}

= 1/2 + {[1/2 + [f(x) - f2(x)] - 1/4 - [f(x) - f2(x)] - f(x) + f2(x)]}

= 1/2 + [1/4 - f(x) + f2(x)] ≠ f(x).

Please make sure the query description is correct.

We would request you to clarify / provide additional details so that we may answer this to the best of the ability.

Regards,

Team,

TopperLearning.

 

Answered by  | 21st Aug, 2009, 07:40: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.